2017
DOI: 10.1002/adfm.201701542
|View full text |Cite
|
Sign up to set email alerts
|

Wafer‐Scale Single‐Crystalline Ferroelectric Perovskite Nanorod Arrays

Abstract: 1D ferroelectric nanostructures are promising for enhanced ferroelectric and piezoelectric performance on the nanoscale, however, their synthesis at the wafer scale using industrially compatible processes is challenging. In order to advance the nanostructure-based electronics, it is imperative to develop a silicon-compatible growth technique yielding high volumetric density and an ordered arrangement. Here, a major breakthrough is provided in addressing this need and ordered and close-packed single crystalline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Moreover, the distribution of the PZT nanorods became more and more dense as the mass ratio of PZT/P­(VDF-TrFE) increased from 1:20 to 1:3. The XRD patterns presented in Figure S3a show the coexistence of tetragonal PZT and the β-phase of P­(VDF-TrFE) in the composite . The FT-IR spectra in Figure S3b and the corresponding variation of β-phase contents with the influence of the PZT/P­(VDF-TrFE) mass ratio shown in Figure S3c were confirmed.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, the distribution of the PZT nanorods became more and more dense as the mass ratio of PZT/P­(VDF-TrFE) increased from 1:20 to 1:3. The XRD patterns presented in Figure S3a show the coexistence of tetragonal PZT and the β-phase of P­(VDF-TrFE) in the composite . The FT-IR spectra in Figure S3b and the corresponding variation of β-phase contents with the influence of the PZT/P­(VDF-TrFE) mass ratio shown in Figure S3c were confirmed.…”
Section: Resultsmentioning
confidence: 98%
“…The XRD patterns presented in Figure S3a show the coexistence of tetragonal PZT and the β-phase of P(VDF-TrFE) in the composite. 46 The FT-IR spectra in Figure S3b and the corresponding variation of β-phase contents with the influence of the PZT/P(VDF-TrFE) mass ratio shown in Figure S3c were confirmed. It was found that the β-phase content increased from 62% to 70.5% when the mass ratio of PZT/P(VDF-TrFE) was 1:10, indicating the piezoelectric ceramic filler's nucleation role in the P(VDF-TrFE).…”
Section: Resultsmentioning
confidence: 99%